2012
DOI: 10.1105/tpc.112.097139
|View full text |Cite
|
Sign up to set email alerts
|

A Chloroplast Light-Regulated Oxidative Sensor for Moderate Light Intensity in Arabidopsis

Abstract: The transition from dark to light involves marked changes in the redox reactions of photosynthetic electron transport and in chloroplast stromal enzyme activity even under mild light and growth conditions. Thus, it is not surprising that redox regulation is used to dynamically adjust and coordinate the stromal and thylakoid compartments. While oxidation of regulatory proteins is necessary for the regulation, the identity and the mechanism of action of the oxidizing pathway are still unresolved. Here, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 67 publications
(97 reference statements)
10
82
0
Order By: Relevance
“…6, its intermolecular disulfide reaction intermediates. Protein blot analysis of denatured, but not reduced, plant extracts identified three intermolecular disulfide-linked ACHT4-containing protein complexes, verified by their susceptibility to chemical reduction by DTT (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6, its intermolecular disulfide reaction intermediates. Protein blot analysis of denatured, but not reduced, plant extracts identified three intermolecular disulfide-linked ACHT4-containing protein complexes, verified by their susceptibility to chemical reduction by DTT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…chloroplast-localized Trxs that have an atypical redox-active site, and a less reducing redox midpoint potential than that of canonical chloroplast Trxs, and that were shown to be good catalysts of 2-Cys Prx reduction, but not of malate dehydrogenase, in vitro (19). Study of the thylakoids-associated ACHT1 revealed that it transmits a disulfide-based oxidative signal in feedback regulation of photosynthesis under homeostasis growth conditions (6). ACHT1 oxidation is driven by 2-Cys Prx, a peroxidase with a low K m for hydrogen peroxide (20)(21)(22) that is conceivably required for the low level of ROS that are typical in signaling events.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…These molecules comprise the reductive pool of the cell and react directly with oxidizing agents or through enzymatic reactions mediated by the different antioxidant enzymes listed above (Mittler, 2002). Controlled by the cellular antioxidant system, ROS is a key signaling factor that mediates acclimation responses to environmental stress conditions (Foyer and Noctor, 2003;Mittler et al, 2004;D'Autréaux and Toledano, 2007;Dangoor et al, 2012). Recent reports proposed an important role for ROS metabolism in algal response to environmental stress, such as iron limitation, allelopathy, UV stress, photo-acclimation and oxidative stress (Rijstenbil, 2002;Sukenik et al, 2002;Vardi et al, 2002Vardi et al, , 2007Janknegt et al, 2008;Li et al, 2009;Murik and Kaplan, 2009;Fischer et al, 2012;Thamatrakoln et al, 2012;Graff van Creveld et al, 2014;Murik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%